(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
It is believed that task-based instruction language teaching prepared a convenient condition and chance for L2 acquisition. This is the reason why tasked-based instruction teaching has been highlighted by many L2 languages in instructors and even syllabus designer. However there would be some differences in L2 learners written performance in different kinds of genre with regard to the effect of tasked based instruction. This paper intended to find and examine the effect of genretic features of four types of genre as descriptive, narrative, argumentative and expository in order to measure fluency, accuracy and complexity. To reach the aim of the study, 120 essay samples of 30 intermediate students were analyzed. The most important goal of this study is to analyze task complexity for selecting, sequencing and even grading material in syllabus designing for task and syllabus designer.